Hubungan Self Efficacy dengan Motivasi Kerja Perawat Rawat Inap di Rumah Sakit Islam Banjarmasin - Ahmad Yoga Saputra; Ida Sa'diatul Hayati; Noor Amaliah; Yustan Azidin (Jurnal Siti Rufaidah, 2025)
Nurses’ performance plays a vital role in ensuring the quality of healthcare services provided to patients. However, in Indonesia, nurses’ performance remains relatively low, which is partly attributed to inadequate levels of work motivation. Work motivation itself is shaped by several factors, one of the most influential being self-efficacy, defined as an individual’s confidence in their ability to perform tasks effectively. This study aimed to investigate the relationship between self-efficacy and work motivation among inpatient nurses at Banjarmasin Islamic Hospital. A quantitative correlational design with a cross-sectional approach was used. The study population included all 75 inpatient nurses, with 63 participants selected through quota sampling. Data collection employed two instruments: a self-efficacy questionnaire adapted from Basari’s research and a work motivation questionnaire developed by Mubarok. The collected data were analyzed using the Spearman rank correlation test with a 0.05 significance level. Findings revealed that most nurses (76.2%) had moderate levels of self-efficacy, while the majority also reported moderate levels of work motivation (55.6%). Statistical testing indicated a correlation coefficient (r) of 0.510 and a significance value (p = 0.001), demonstrating a moderate, positive, and statistically significant relationship between self-efficacy and work motivation. These results suggest that the stronger a nurse’s belief in their competence, the greater their motivation to perform work-related tasks. The study concludes that self-efficacy is a critical determinant of work motivation among inpatient nurses, highlighting the need for hospital management to implement strategies that strengthen nurses’ confidence and abilities. Interventions such as training, mentoring, and continuous professional development are recommended to enhance self-efficacy, which in turn can improve work motivation and overall performance, thereby contributing to higher-quality healthcare delivery.